Sustainability reporting in Brazil:: an Analysis of the its Use in the Financial and Energy Services Sectors (Sustainability in Debate, 2014)
The discussions about the theme sustainability have intensified itself in recent times. The concernsabout environmental and social questions aggregate itself alongside economic concerns. Therewas an increase of the companies that communicate the strategies of sustainability through asustainability reporting. The model of reporting of the Global Reporting Initiative is consideredone of most utilized in the international context. This study aims to investigate an evolution ofdegree of adherence full (GAPIE-GRI) and the degree of effective disclosure (GEE) to the socialperformance (labor practices and decent work and human rights) of Brazilian companies in the sectors of financial services, energy and public service energy, which published the GRI sustainabilityreport between 2007 to 2009. It was observed that the companies had median results in indicesGAPIE-GRI and GEE. The energy sector showed higher rates compared to the financial servicesindustry. There was an evolution in communication and commitment to effective communicationof social performance.